Research on the Relationship Between College Students’ Participation in Sports Activities and Self-Harmony Assessment Based on the Moderating and Mediating Effects of Mental Toughness - Xu, Haixiao (Frontiers in Psychology, 2022)
College students are the future of the motherland, the hope of the nation, and the reserve force to realize the great rejuvenation of the Chinese nation. The period of college students is an important period for the formation of ideals, beliefs and world views. However, due to the contradictions between physiological maturity and psychological maturity, and the contradictions between independent consciousness and cognitive ability in the growth process of college students, it is easy to cause the internal psychological problems of inconsistency and disharmony. Correct sports lifestyle is conducive to promoting individual self-harmony. In the daily life and learning process of college students, the role of self-harmony is often ignored and not paid enough attention to. This indicates that it is necessary to further study the effect of physical activity on adolescents’ self-harmony. Mental toughness is one of the important factors affecting self-harmony. Therefore, the variable of mental toughness is introduced to analyze the correlation between physical activity and self-harmony. By analyzing the correlation among sports activities, mental toughness and self-harmony, this study provides theoretical reference for improving and enhancing college students’ self-harmony degree, and provides beneficial suggestions for relevant management departments when making plans.